PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP CUSTOMER LIFETIME VALUE DAN KEPUASAN PELANGGAN SEBAGAI VARIABEL PEMEDIASI PADA PAMELLA SUPERMARKET YOGYAKARTA - Evrita Putri Azzahroh Evrita (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2021)
ABSTRACT The development of retail industry in Indonesia in 2017 was declining, based on the results of a survey conducted by global management consulting firms in the Global Retail Development Index (GRDI) report, showing that Indonesia was at the 8th rank compared to the previous year which was at the 5th place. The decline, however, was inversely proportional to the condition of Pamella supermarket which continued to open new branches. This study aimed to see and reveal the effect of customer relationship management on customer lifetime value and customer satisfaction as mediating variables. The objects of this study were the customers of Pamella supermarket. The data were collected through questionnaires which were distributed to the customers of Pamella supermarket who had become customers for more than two years. There were 200 respondents involved in this study. The method used in this study was a quantitative method while the data were in the form of primary data. The analytical tool used in this study was PLS with SmartPLS 3.8 software. The results in this study proved that customer relationship management strategy could positively and significantly result in customer satisfaction and customer lifetime value. This study also showed that customer satisfaction could serve as full or complete mediation. Kata Kunci: Customer relationship management, Customer satisfaction, Customer lifetime value, Pamella supermarket